Research trends in library and information science in Philippine universities - Reji Chandra, D. T. (Institute of Library Science, University of the Philippines Diliman, 1981)
This study is about the research trends in Library and Information Science in the Philippine universities offering graduate studies in the field. One hundred and fifty nine theses and special problems done in the six universities in the Philippines were studied to collect data. The six universities are Philippine Normal College, Philippine Women's University, University of San Carlos, University of Santo Tomas, University of the East, and University of the Philippines.